2019
DOI: 10.14393/bj-v35n2a20198-42730
|View full text |Cite
|
Sign up to set email alerts
|

The effect of banana leaf package on the shelf life of rainbow trout fillet in comparison with plastic bags

Abstract: The aim of this study was to evaluate the effect of banana leaf extract on the quality and shelf life of rainbow trout compared to plastic bags at freezing temperature for 40 days. For evaluating this propose, the antioxidant activity of banana leaf extract was assessed. In addition, the shelf life of fish filets was determined by measuring thiobarbituric acid (TBA) and pHof fish. The banana leaves extract showed the highest content of vitamin E (5.8 ± 0.61 mg /g) and carotenoids (12.8 ± 0.1 mg /g). The potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…BPE of M. acuminata successfully prevented oxidation of fish oil (Anal et al, 2014) and concentrate as well as freshly squeezed orange juices (Ortiz et al, 2017). Ahmadi et al (2019) demonstrated the effects of banana leaf extract on the consistency and shelf life of rainbow trout fillet, compared with freezing in plastic bags for 40 days. The extract successfully inhibited lipid oxidation in the fish fillet during freezing, which may be attributed to its high antioxidant capacity.…”
Section: Natural Antioxidantmentioning
confidence: 86%
See 2 more Smart Citations
“…BPE of M. acuminata successfully prevented oxidation of fish oil (Anal et al, 2014) and concentrate as well as freshly squeezed orange juices (Ortiz et al, 2017). Ahmadi et al (2019) demonstrated the effects of banana leaf extract on the consistency and shelf life of rainbow trout fillet, compared with freezing in plastic bags for 40 days. The extract successfully inhibited lipid oxidation in the fish fillet during freezing, which may be attributed to its high antioxidant capacity.…”
Section: Natural Antioxidantmentioning
confidence: 86%
“…Banana leaves are large, may be 2.7 × 0.6 m in size, flexible, and waterproof. They are suitable for packaging and serving foods due to their large waxy surface (Ahmadi et al, 2019). They are also rich in fibers, flavonoids, polyphenols, and tannins (Al-Mqbali & Hossain, 2019).…”
Section: Banana Plant Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bananas are considered to be a valuable dietary component due to their high content of dietary fiber, essential vitamins, and minerals. Banana peel makes up around half of the total mass of the fruit (35%–50%) out of all by‐products of the banana such as pseudo‐stems, leaves, and blossoms (Ahmadi et al, 2019; Gomes et al, 2022). The banana pseudo‐stem (BPS) grows around 6–7.6 m tall, bears flowers, leaves, and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Banana leaves are large, flexible, waterproof, and around 2.7 × 0.6 m in size. Due to their substantial waxy surface, they are appropriate for food packaging and food serving (Ahmadi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%